2020
DOI: 10.3389/fnhum.2020.560860
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Follow-Up on Pediatric Cases With Congenital Myasthenic Syndromes—A Retrospective Single Centre Cohort Study

Abstract: Introduction: Congenital myasthenic syndromes (CMS) refer to a heterogenic group of neuromuscular transmission disorders. CMS-subtypes are diverse regarding exercise intolerance and muscular weakness, varying from mild symptoms to life-limiting forms with neonatal onset. Long-term follow-up studies on disease progression and treatment-response in pediatric patients are rare.Patients and Methods: We analyzed retrospective clinical and medication data in a cohort of 32 CMS-patients including the application of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…On average, children included in the current study were diagnosed over 4 years after initial symptoms were observed, matching the delay described in literature 7 . Consistent with prior findings, the majority of patients presented with symptoms in first month of life 4 . Ideally, children should be diagnosed shortly after.…”
Section: Discussionsupporting
confidence: 85%
“…On average, children included in the current study were diagnosed over 4 years after initial symptoms were observed, matching the delay described in literature 7 . Consistent with prior findings, the majority of patients presented with symptoms in first month of life 4 . Ideally, children should be diagnosed shortly after.…”
Section: Discussionsupporting
confidence: 85%
“…There are no relevant biomarkers for CMS and the diagnosis is usually achieved through neurophysiology [97]. Indeed, CK concentrations are usually normal in CMS [97], but there are reported cases in which CK and aldolase concentrations can be mildly elevated [98,99]. In these cases, elevated CK is due to a phenomenon called endplate myopathy [99].…”
Section: Congenital Myasthenic Syndromesmentioning
confidence: 99%
“…RMW is common and comprises early-onset weakness of respiratory and oropharyngeal muscles, as well as musculoskeletal deformities. Respiratory failure is common in patients with dysphagia [51][52][53].…”
Section: Congenital Myasthenic Syndromementioning
confidence: 99%